Job stress and Employee Assistance Programs (EAPs) among police personnel at Royal Police Headquarters in Kuching / Nur Sushila Johari and Syaima Ismail - Johari, Nur Sushila; Ismail, Syaima (2014)
Police personnel work in a wide variety of environments under different circumstances and part of the work involves stressful situations. Job stress is increasingly becoming an epidemic in the work environment. Psychological and physiological strain from work increases the risk of job stress. This research study focuses on the job stress and Employee Assistance Programs (EAPs) among police personnel at Royal Police Headquarters in Kuching. Organizations can help reduce the overall effects of job stress by developing and implementing prevention and intervention methods to help employees manage and cope with job stress. To reduce job stress of police personnel, this study suggests several measures along with Employee Assistance Programs (EAPs). This programme is focused on the employee’s total mental and physical condition. There are five main objectives in this research study which includes to identify the level of stress among police personnel, to study the stressors that affect the police personnel, to study the relationship between stressors and the need of EAPs among police personnel, to identify the feedbacks among police personnel about the need of EAPs and lastly to provide recommendations for the police personnel on how to improve EAPs in order to reduce their stress level. A random sampling of 120 respondents is being selected from all level of the department in the Royal Police Headquarters in Kuching. This research study are using questionnaires to collect the information and data from the respondents. The results has shown that the police personnel was not experienced a high level of stress and the highest stressors affect them is work environment due to poor equipment, excessive paperwork, lack of recognition and operational stressors such as hoax cqlls, missing meals, dealing with the public. Our findings also focus on to identify the relationship of stressors and the need of Employee Assistance Programs (EAPs). Based on the result, it shows stressors which are management, co-workers and work environment statically significant with very weak relationship. This paper therefore provides not only information on stress factors, but also sheds light on how the level of stress and stressors can be reduced through the need of EAPs.